Tim-3-expressing macrophages are functionally suppressed and expanded in oral squamous cell carcinoma due to virus-induced Gal-9 expression - Jianfeng Dong; Lijun Cheng; Minchao Zhao; Xiangfeng Pan; Zhiqiang Feng; Dawei Wang (Tumor Biology)
Oropharyngeal head and neck squamous cell carcinoma is a common malignant tumor in the oral cavity. High-risk human papillomavirus 16 infection is a major cause of oropharyngeal head and neck squamous cell carcinoma development. Strong antitumor immune responses, especially CD8 + T cell responses, are thought to be essential to effective cancer treatment and are associated with better prognosis in oropharyngeal head and neck squamous cell carcinoma. In this study, we examined the role of the Tim-3/Gal-9 pathway in oropharyngeal head and neck squamous cell carcinoma patients. We found that Gal-9 expression by CD4 + T cells was increased in human papillomavirus-positive oropharyngeal head and neck squamous cell carcinoma patients, but not in human papillomavirus-negative oropharyngeal head and neck squamous cell carcinoma patients. Increased Gal-9 secretion by CD4 + T cells presented multiple immunosuppressive effects. Coculturing monocytes with high Gal-9-expressing CD4 + T cells resulted in the expansion of Tim-3 + monocytes, which suppressed interferon gamma production by activated CD8 + T cells. Subsequently, total monocytes incubated with exogenous Gal-9, or high Gal-9-expressing CD4 + T cells, suppressed the expression of interferon gamma by CD8 + T cells. Exogenous Gal-9 and high Gal-9-expressing CD4 + T cells also suppressed the secretion of both interleukin 10 and interleukin 12 by monocytes. These effects are Tim-3/Gal-9-dependent because blocking Tim-3 and/or Gal-9 could enhance the support of CD8 + T cell interferon gamma production and the interleukin 10 and interleukin 12 secretion by monocytes. Together, these data suggest that the high Tim-3 expression in monocytes could be utilized by tumor-promoting Gal-9 expression on CD4 + T cells. Immunotherapy in human papillomavirus-positive oropharyngeal head and neck squamous cell carcinoma patients therefore faces an additional challenge posed by Tim-3 and Gal-9 and likely requires the blockade of these molecules.